Seismic evidence for the stratified lithosphere in the south of the North China Craton. Issue 2 (12th February 2013) - Wang, Pan; Xu, Mingjie; Wang, Liangshu; Mi, Ning; Yu, Dayong; Li, Hua; Li, Cheng; Bao, Xuewei; Huang, Tao; Huang, Hui
Abstract: [1] The North China Craton (NCC) formed in the Paleoproterozoic and suffered cratonic destruction in the Mesozoic. It consists of the Western NCC (WNCC), the Trans‐North China Orogen (TNCO) and the Eastern NCC (ENCC). We investigated the upper mantle structures in the southern NCC by using receiver functions analysis. Polarization analysis was applied to increase the quality of receiver functions. The seismic images show significant stratified structures in the upper mantle in the south of the NCC. In the south of the WNCC, the lithosphere is ~280 km thick and contains a low‐velocity zone at ~110–220 km depth. This low‐velocity zone is interpreted as an intracratonic partial melting zone. In the south of the TNCO and ENCC, there is a low‐velocity zone at ~60–200 km depth, which results from the partial melting during the Mesozoic cratonic destruction. Its upper boundary is interpreted as new Lithosphere‐Asthenosphere Boundary at ~60–100 km depth. Below this low‐velocity zone, there are the remains of Archean lithosphere (RAL). Blocks of RAL stagnate in the asthenosphere and reach depths over 300 km. A high‐velocity slab extends from the uppermost mantle of the WNCC into the RAL with a dip‐angle of ~20°. This slab is interpreted as the Paleoproterozoic slab, which indicates an eastward subduction between the WNCC and the ENCC. The WNCC is stable. The lithosphere in the south of the TNCO and ENCC suffered the Mesozoic cratonic destruction, while the destruction is relatively weaker than that in the north of the ENCC. Key Points: Intra‐cratonic partial melting zone is in the cratonic mantle lithosphere Remains of Archean Lithosphere stagnate in the asthenosphere Imaged high‐velocity slab indicates an eastward subduction at ~1.85 Ga